Optimization of Fluidized Bed Combustion of Semirara Coal - Elauria, Jessie C.; Cruz, Ibarra E. (Philippine Engineering Journal, 2021)
A study was conducted to determine the suitability of local coal as fuel in fluidized bed combustor (FBC) and to establish the optimum operating conditions of the FBC unit. A 6-inch diameter reactor with Pampanga river sand (mean particle size of 1.139 micrometer) as inert bed material was used in the conduct of the experiment. Combustion tests were run at air flow rates of 180 and 260 L/min, A/F ratios of 7.6 and 11.0 kg of dry air per kg of fuel, bed depths of 6 and 9 inches and bed temperatures of 820 and 910 C. Coal sizes -1/16 + 1/32, -1/8 + 1/16, and -1/4 + 1/16 inch were evaluated based on their fluidization characteristics prior to experimentation.  Coal size of -1/16 + 1/32 inch registered a minimum fluidizing velocity close to that of the bed material but coal size of -1/16 + 40 mesh is recommended due to higher recovery during size reduction. Combustion efficiency ranged from 52 to 98 percent, while heat output rates ranged from 1,438 to 3,295 Keal/kg of fuel equivalent to 27.6 and 63.3 percent thermal efficiencies. Combustion and thermal efficiencies are directly affected by air flow, A/F ratio and bed depth. Temperature is also positively related to thermal efficiency. The optimum performance of the FBC unit was found to be at bed temperature range from 902 to 910 C, A/F ratio of 11.0 and 11.6, air flow of 260 to 285 L/min and bed depth of 9.0 to 11.1 inches. The study as a whole showed that low quality coal (low heating value and high ash content) such as Semirara is a viable fuel in fluidized bed combustor.